Antimicrobial activity of Cymbopogon schoenanthus essential oil extracted by a solar distillation system - Safa, Zineb; Boulal, Ahmed; Zahra Hadef, Khawla; Djenadi, Katia (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Cymbopogon schoenanthus (L.) Spreng is an aromatic medicinal plant that grows in Algeria. It is commonly called camel grass and known by the local name "Lemmad." Traditionally, it has been used to treat diverse diseases. Therefore, this study aimed to evaluate the antimicrobial activity of the essential oil of Cymbopogon schoenanthus (EOCS), grown in Timiaouine, Algeria, A solar distillation (SD) system was used to extract the oil. This extraction occurred in June 2023. Subsequently, the physical properties were determined. The antimicrobial activity against four bacteria and one yeast was evaluated using the agar diffusion test. Various dilutions were used, and the inhibition zones were measured to determine the extent of antimicrobial activity. In this study, the yield was estimated to be 0.97 %, with a density of 0.8490 and a refractive index of 1.4850. The antimicrobial properties of this essential oil (EO) showed efficacy against Escherichia coli (EC) and Klebsiella pneumoniae (KP) at dilutions of 1/3 and 1/4, with inhibition diameters varying between 15 to 9 mm. On the other hand, other strains showed resistance throughout all dilutions. This research indicates that the EOCS extracted using the SD process has effective antibacterial properties against Gram- bacteria. Moreover, Additional research is required to clarify and assess the effects of the chemical composition, thereby enhancing our understanding of the underlying mechanism.